Comparative Evaluation of Levo-Bupivacaine against Ropivacaine for Post-Operative Pain Relief in Patients of Laparoscopic Appendectomy - Panjiyar, Shyam Kishor; Goel, Ravi (Innovative Journal of Medical and Health Sciences, 2020)
Introduction: Pain in the immediate postoperative period is less after laparoscopic surgery than conventional surgical techniques. Ropivacaine is often in favored over Bupivacaine to avoid toxicity. Levo-bupivacaine a newer version of bupivacaine is said to be safer than Ropivacaine. We have evaluated the pain relief provided by Ropivacaine and Levo-bupivacaine instilled intra-abdominally during laparoscopic surgery for acute appendicitis. Methods and material: In a randomized placebo controlled study conducted on 90 patients in private medical institute over a period of year, a patient control analgesia (PCA) total amount of morphine utilized to attain pain scores of 0-1 was measured in placebo, Ropivacaine and Levo-bupivacanie group using visual analog score (VAS). Data was analyzed using analysis of variance and tests of statistical significance were employed. Results: Significant difference was not observed between the Ropivacaine and Levo-bupivacaine groups with similar utilization of morphine for both drugs. Whereas significant difference was noted between placebo and local anaesthetics. Conclusions: There appear to be no difference between Ropivacaine and Levo-bupivacaine in terms of pain relief. Pre-emptive instillation of local anaesthetic for laparoscopic surgery is beneficial for post-operative pain relief.